THEORETICAL AND LEGAL ANALYSIS OF THE STAGES OF FORMATION OF LABOR LEGISLATION - Dyban, Maksym (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Objective: to conduct a thorough analysis of the evolution of human rights at different stages of development of society, to study the main aspects of the formation of socio-legal status of man in the field of labor. Research methods: general scientific and special methods are used in the work. Results: the peculiarities of the formation and development of labor legislation are analyzed, specificity of the factory legislation in the period of activization of labor movement for labor rights is defined, it is established that «formation of the social status of the person in labor sphere» is formation and development of labor rights, duties. The stages of formation of the social status of a person in the sphere of labor are singled out, namely: 1) collective-dependent (primitive-communal); 2) individually dependent (slave, feudal); 3) factory-industrial (capitalist); 4) collective-totalitarian (Soviet period); 5) integration-European (modern development of Ukraine). It is established that the specificity of primitive society is the collective organization of labor at the initial stage of human life, namely the need for collective efforts to organize life, because man himself was unable to earn a living. Discussion: the question of the social and legal position of man in the field of labor shows that it is work that most fully reflects the level of socialization of man, his motivation, as well as needs. Trends in social evolution indicate the patterns of formation of human social status at different stages of formation of society and the development of labor legislation. Features of historical and legal aspects of formation of the labor legislation in the XX-XXI centuries are considered.